KONSTRUKSI METODOLOGI TEOLOGI FEMINISME - Esha, Muhammad Inâ€™am (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2006)
This Article studies about methodology construction used in feminism theology. Riffat Hassanâ€™s thought made as a model in this article. There are several things which can be understood in this article namely: First, feminism theology which emerges in domain of modern Islamic thought cannot be discharged from a global tendency of this discourse growth in America. Second, in the context of â€œIslamicateâ€, the emergence of feminism theology is pushed by a social reality in Islamic societyÂ which still have discrimination and subjugation toward woman. Particularly, this matter is legitimized by religious doctrines. Third, methodologically speaking, feminism theology has been reconstructed by using ideal, historical and empirical-normative approaches as well as by deconstruction, hermeneutic and hadits criticism methods. By these approaches and methods, feminism theology becomes one of discourses forÂ woman to fight againts discrimination and subjugation